Pengembangan Sistem Manajemen Penanggulangan Lingkungan Kotor dan Bank Sampah berbasis Web (Studi Kasus : Kelurahan Dampit) - Willy Christian Putra; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Dampit waste bank is an organization engaged in the utilization of waste management that has been running by having 200 clients. Waste bank clients collect garbage and save it to the waste bank for later input into the client's savings book and recorded on the officer's ledger. The management process at the waste bank is still uses manual method using books or archives. Dampit Waste Bank has problems in terms of waste bank management where officers have difficulty in making transactions because recording transactions is done conventionally in the savings book. From waste bank clients side also find it difficult because they have difficulty seeing the total balance and information about the waste price list updates. Another problem that occurs is the lack of information about the environmental conditions of Dampit Village. The Dirty Environment Management System and Waste Bank were developed to help realize the goals of the Dampit Waste Bank organization and also help solve problems in the transaction process at the Dampit Waste Bank. System development was performed using the waterfall model with an object-oriented approach. This system was tested using the whtebox technique in unit and integration testing and used the blackbox technique in validation testing. The development of the system was produced a system that can solve problems in terms of transactions by waste bank officers and customers and also can report a dirty environment to find volunteers, especially in the Dampit Village area.